A film material for power battery packaging and a preparation method thereof

CN120363561BActive Publication Date: 2026-11-03广东鸿升新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510474423.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2026-11-03
Estimated Expiration
2045-04-16

AI Technical Summary

Technical Problem

Existing power battery encapsulation films are prone to softening and deformation at high temperatures, have poor oxygen permeability, low mechanical strength, and poor interface stability, and cannot simultaneously meet the requirements for high-temperature protection, thermal management, mechanical strength, and interface stability.

Method used

The product adopts a layered structure design. The outer high-temperature resistant barrier layer is composed of polyetheretherketone substrate, nano-silica, nano-alumina and fluorinated carbon nanotubes. The gradient transition layer is composed of a gradient spun fiber layer of nano-alumina and polyimide. The middle tear-resistant barrier layer is a high-density polyethylene layer with nano-silica/polyvinylidene fluoride composite coating. The inner adhesive layer is an irradiated cross-linked ethylene-vinyl acetate copolymer layer. It is formed in one step by a five-layer co-extrusion equipment and reinforced by maleic anhydride grafted polypropylene.

Benefits of technology

It improves the high-temperature protection capability, thermal management performance, mechanical strength and interface stability of the membrane material, delays the spread of thermal runaway, enhances the resistance to external impact, reduces oxygen permeability, adapts to the mechanical stress of the battery under complex working conditions, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120363561B_ABST
    Figure CN120363561B_ABST
Patent Text Reader

Abstract

The application provides a film material for power battery packaging and a preparation method thereof, and belongs to the field of battery packaging materials. The layer structure of the film material is as follows from outside to inside: an outer high-temperature-resistant barrier layer, a gradient transition layer, an intermediate tear-resistant barrier layer, and an inner adhesive layer. The outer high-temperature-resistant barrier layer is composed of a polyether ether ketone base material, nano-silicon dioxide, nano-aluminum oxide, and carbon fluoride nanotubes. The gradient transition layer is composed of a gradient spinning fiber layer of nano-aluminum oxide and polyimide. The intermediate tear-resistant barrier layer is a high-density polyethylene layer with a nano-silicon dioxide / polyvinylidene fluoride composite coating on the surface, and phase change microcapsules are embedded in the high-density polyethylene layer. The inner adhesive layer is an irradiation cross-linked ethylene-vinyl acetate copolymer layer. The layered structure of the film material for power battery packaging is reasonably designed, so that the high-temperature protection, thermal management, mechanical strength, and interface stability of the film material for power battery packaging are simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery packaging materials technology, and in particular to a film material for power battery packaging and its preparation method. Background Technology

[0002] Batteries are the "heart" of new energy vehicles, and their performance directly determines the vehicle's range, safety, and cost. Encapsulation films, as one of the core components of batteries, undertake multiple functions, including cell protection, insulation sealing, thermal management, and weight reduction. Statistics show that power batteries account for more than 40% of the total vehicle cost, while encapsulation materials (such as aluminum-plastic films and separators) account for 15-20% of the battery cost. As new energy vehicles develop towards higher energy density and longer lifespan, the technological iteration of encapsulation films has become a focus of the industry.

[0003] Existing encapsulation films are mostly aluminum-plastic composite films, composed of an aluminum foil layer (purity > 99.5%) and a polypropylene (PP) or nylon (PA) layer bonded together with an adhesive, combining the barrier properties of metals with the flexibility of plastics. However, aluminum-plastic films have poor oxygen permeability (prone to vapor accumulation and mold growth in humid environments), and the plastic layer (such as LDPE) has low tear strength. Furthermore, the PP / PA layer is prone to softening and deformation at high temperatures (> 120°C), leading to encapsulation failure. Therefore, how to simultaneously improve the high-temperature protection, thermal management, mechanical strength, and interfacial stability of films used for power battery encapsulation is a pressing technical problem that needs to be solved. Summary of the Invention

[0004] This application provides a film material for power battery encapsulation and a method for preparing the same, in order to solve the following technical problem: how to simultaneously improve the high-temperature protection, thermal management, mechanical strength and interface stability of the film material used for power battery encapsulation.

[0005] In a first aspect, this application provides a film material for power battery encapsulation, wherein the layer structure of the film material, from the outside to the inside, comprises: an outer high-temperature resistant barrier layer, a gradient transition layer, an intermediate tear-resistant barrier layer, and an inner adhesive layer; wherein,

[0006] The outer high-temperature resistant barrier layer is composed of polyetheretherketone substrate, nano-silica, nano-alumina and fluorinated carbon nanotubes;

[0007] The gradient transition layer is composed of a gradient spun fiber layer of nano-alumina and polyimide;

[0008] The intermediate tear-resistant barrier layer is a high-density polyethylene layer with a nano-silica / polyvinylidene fluoride composite coating on the surface, and phase change microcapsules are embedded in the high-density polyethylene layer.

[0009] The inner adhesive layer is an irradiated cross-linked ethylene-vinyl acetate copolymer layer.

[0010] Optionally, the thickness of the outer high-temperature resistant barrier layer is 50–80 μm;

[0011] The thickness of the gradient transition layer is 20–30 μm;

[0012] The thickness of the intermediate tear-resistant barrier layer is 80–120 μm;

[0013] The thickness of the inner adhesive layer is 30–50 μm.

[0014] Optionally, the mass of the nano-silica is 5-8% of the mass of the outer high-temperature resistant barrier layer;

[0015] The mass of the nano-alumina is 3 to 5% of the mass of the outer high-temperature resistant barrier layer;

[0016] The mass of the fluorinated carbon nanotubes is 1 to 3% of the mass of the outer high-temperature resistant barrier layer.

[0017] Optionally, the fluorinated carbon nanotubes are treated with CF4 plasma, and the surface fluorination rate of the fluorinated carbon nanotubes is 30-50%.

[0018] The particle size of the nano-silica is 30-50 nm;

[0019] The particle size of the nano-alumina is 40–60 nm.

[0020] Optionally, the gradient-spun fiber layer consists of an outer layer, a middle layer, and an inner layer deposited layer by layer by electrospinning process; wherein,

[0021] The outer layer has a nano-alumina content of 4-6%, a thickness of 8-12 μm, and a pore size of 180-200 nm.

[0022] The intermediate layer has a nano-alumina content of 8-12%, a thickness of 7-10 μm, and a pore size of 80-100 nm.

[0023] The inner layer has a nano-alumina content of 13-17%, a thickness of 5-8 μm, and a pore size of 40-60 nm.

[0024] Optionally, the thickness of the nano-silica / polyvinylidene fluoride composite coating is 2-5 μm, and the mass ratio of the nano-silica to the polyvinylidene fluoride is 1:(4-6).

[0025] The phase change microcapsules have a particle size of 100-200 nm, a core material of paraffin / stearic acid composite, a shell material of nano-silica, and a shell thickness of 20-40 nm.

[0026] Optionally, the mass fraction of vinyl acetate in the molecular chain of the ethylene-vinyl acetate copolymer is 5-40%.

[0027] Secondly, this application provides a method for preparing the membrane material according to any embodiment of the first aspect, the method comprising the following steps:

[0028] S1. Polyether ether ketone substrate, nano silica, nano alumina and fluorinated carbon nanotubes are melt-blended using a twin-screw extruder and then hot-pressed to obtain the outer high-temperature resistant barrier layer.

[0029] S2. Nano-alumina and polyimide are dissolved in a solvent in a gradient ratio, and then the outer layer, middle layer and inner layer are sequentially deposited by multi-nozzle electrospinning to obtain the gradient transition layer.

[0030] S3. Disperse the phase change microcapsules in high-density polyethylene melt, and after cooling, coat the surface of high-density polyethylene to form a nano-silica / polyvinylidene fluoride composite coating to obtain an intermediate tear-resistant barrier layer.

[0031] S4. Mix vinyl acetate, ethylene resin and additives and extrude them, then crosslink them by electron beam irradiation to form a three-dimensional crosslinked network, and then perform hot pressing to obtain the inner adhesive layer.

[0032] S5. Using a five-layer co-extrusion equipment, the outer high-temperature resistant barrier layer, the gradient transition layer, the middle tear-resistant barrier layer, and the inner adhesive layer are formed into a four-layer structure in one step, and the layers are reinforced and bonded by maleic anhydride-grafted polypropylene to obtain a film material for power battery encapsulation.

[0033] Optionally, the melt blending temperature is 380–400°C;

[0034] In the electrospinning process, the concentration of the spinning solution is 15-20 wt%, the nozzle diameter is 0.3-0.5 mm, the receiving distance is 15-20 cm, and the voltage is 20-25 kV.

[0035] The electron beam irradiation dose is 12–15 kGy;

[0036] The additives include 0.1-0.5 wt% antioxidant 1010 and 0.5-1.0 wt% calcium stearate;

[0037] The die temperature of the five-layer co-extrusion equipment is 380-400℃. The interlayer bonding is enhanced by maleic anhydride-grafted polypropylene cast film. The grafting rate of the maleic anhydride-grafted polypropylene is 1.0-1.5%, and the addition amount is 1-2% of the total interlayer thickness.

[0038] The fluorinated carbon nanotubes were treated with CF4 plasma at a power of 50–100 W for 10–20 min.

[0039] Optionally, the preparation method of the phase change microcapsules includes:

[0040] Paraffin wax and stearic acid are melt-mixed in a 1:1 mass ratio, then added to an aqueous phase containing emulsifier, and the mixture is passed through a high-shear emulsifier to form a core material emulsion.

[0041] Sodium silicate solution was added dropwise to the core material emulsion as a silica precursor, and an interfacial hydrolysis-condensation reaction was carried out under the catalysis of ammonia water to generate a uniform silica shell and obtain a mixed solution.

[0042] The mixture was centrifuged, washed, and dried sequentially to obtain the phase change microcapsules.

[0043] The technical solutions provided in this application have the following advantages compared with the prior art:

[0044] This application provides a membrane material for power battery encapsulation. The membrane material's layer structure, from the outside to the inside, comprises: an outer high-temperature resistant barrier layer, a gradient transition layer, a middle tear-resistant barrier layer, and an inner adhesive layer. The outer high-temperature resistant barrier layer is composed of a polyetheretherketone (PEEK) substrate, nano-silica, nano-alumina, and fluorinated carbon nanotubes. The gradient transition layer is composed of a gradient spun fiber layer of nano-alumina and polyimide. The middle tear-resistant barrier layer is a high-density polyethylene layer with a nano-silica / polyvinylidene fluoride composite coating on its surface, and phase change microcapsules are embedded within the high-density polyethylene layer. The inner adhesive layer is an irradiated cross-linked ethylene-vinyl acetate copolymer layer. Through a rationally designed layered structure for power battery encapsulation, the PEEK layer resists external heat sources, preventing direct heat transfer; the middle layer absorbs heat during phase change, and the phase change microcapsules absorb heat during thermal runaway, slowing the rate of temperature rise; the gradient layers provide thermal expansion matching, avoiding shear stress between layers due to temperature differences, and improving overall thermal stability. Meanwhile, the outer layer is puncture-resistant, and the middle layer is tear-resistant. The PEEK and HDPE form a "rigid-flexible" composite structure, enhancing resistance to external impacts. The gradient layer buffers vibration, and the porous fiber layer absorbs mechanical vibration energy, reducing the risk of inner layer debonding. It also features a dual-barrier network: an outer layer of nanofiller barrier and a middle layer of dense coating barrier, reducing oxygen permeability. This simultaneously improves the high-temperature protection, thermal management, mechanical strength, and interface stability of the membrane material used for power battery encapsulation. Attached Figure Description

[0045] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0046] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0047] Figure 1 A schematic diagram of the structure of a film material for power battery encapsulation provided in an embodiment of this application;

[0048] Figure 2 A schematic flowchart illustrating a method for preparing a film material for power battery encapsulation, provided in an embodiment of this application;

[0049] Figure label:

[0050] 1-Outer high-temperature resistant barrier layer, 2-Gradient transition layer, 21-Outer layer, 22-Middle layer, 23-Inner layer, 3-Middle tear-resistant barrier layer, 4-Inner adhesive layer. Detailed Implementation

[0051] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0052] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0053] Figure 1 This is a schematic diagram of the structure of a film material for power battery encapsulation provided in an embodiment of this application.

[0054] like Figure 1 Therefore, this application provides a film material for power battery encapsulation, wherein the layer structure of the film material, from the outside to the inside, is as follows: an outer high-temperature resistant barrier layer, a gradient transition layer, a middle tear-resistant barrier layer, and an inner adhesive layer; wherein,

[0055] The outer high-temperature resistant barrier layer is composed of polyetheretherketone substrate, nano-silica, nano-alumina and fluorinated carbon nanotubes;

[0056] The gradient transition layer is composed of a gradient spun fiber layer of nano-alumina and polyimide;

[0057] The intermediate tear-resistant barrier layer is a high-density polyethylene layer with a nano-silica / polyvinylidene fluoride composite coating on the surface, and phase change microcapsules are embedded in the high-density polyethylene layer.

[0058] The inner adhesive layer is an irradiated cross-linked ethylene-vinyl acetate copolymer layer.

[0059] In some embodiments, the thickness of the outer high-temperature resistant barrier layer is 50–80 μm;

[0060] The thickness of the gradient transition layer is 20–30 μm;

[0061] The thickness of the intermediate tear-resistant barrier layer is 80–120 μm;

[0062] The thickness of the inner adhesive layer is 30–50 μm.

[0063] It should be noted that the functions of each layer are as follows:

[0064] Outer high-temperature resistant barrier layer (50-80μm): The polyetheretherketone (PEEK) substrate is heat resistant to >250℃, preventing the outer layer from melting or deforming during battery thermal runaway (such as localized high temperatures during a short circuit); simultaneously, nano-silica and alumina form a rigid network with a puncture resistance ≥50MPa (superior to traditional aluminum-plastic films); fluorinated carbon nanotubes construct conductive pathways with a surface resistivity ≤10. 6 Ω prevents short circuits caused by static electricity buildup; in addition, the densely stacked nanofillers have an oxygen permeability close to that of aluminum foil.

[0065] Gradient transition layer (20-30μm): The content of nano-alumina varies in a gradient, causing the coefficient of thermal expansion to change from 5×10⁻⁶ in the outer layer. -6 / ℃ (matching PEEK) Smoothly transition to the middle layer 12×10 -6 / ℃ (matching HDPE) to avoid thermal stress delamination; at the same time, the electrospun fiber layer (outer layer pore size 200nm → inner layer 50nm) forms a gradient pore structure to absorb mechanical vibration energy during charge and discharge cycles; in addition, the dense inner layer (50nm pore size) works in conjunction with the outer layer to block water and oxygen permeation.

[0066] Intermediate tear-resistant barrier layer (80-120μm): The high-density polyethylene (HDPE) matrix has a tear strength ≥40MPa, supporting the battery encapsulation structure; the phase change microcapsules (phase change enthalpy 160-180J / g) absorb heat at 80-100℃, delaying thermal runaway diffusion; at the same time, the nano-SiO2 / PVDF coating enhances the barrier performance and compensates for the inherent air permeability defects of HDPE; the elastic modulus of HDPE and the inner EVA layer are matched to adapt to the volume changes of battery charging and discharging.

[0067] Inner adhesive layer (30-50μm): The inner layer (adhesive layer) is in direct contact with the battery cell and requires high bonding strength and resistance to electrolyte corrosion. After irradiation cross-linking, the peel strength is enhanced, and it can withstand long-term immersion in electrolyte; at the same time, the flexibility of EVA can absorb the deformation stress of the battery and prevent interface debonding.

[0068] Therefore, this application rationally designs a layered structure for the film material used in power battery encapsulation. The PEEK layer resists external heat sources and prevents direct heat transfer; the middle layer absorbs heat through phase change, and the phase change microcapsules absorb heat during thermal runaway, slowing down the rate of temperature rise; the gradient layer matches thermal expansion, avoiding shear stress between layers due to temperature differences and improving overall thermal stability. Simultaneously, the outer layer is puncture-resistant, and the middle layer is tear-resistant. The PEEK and HDPE form a "rigid-flexible" composite structure, enhancing resistance to external impacts. The gradient layer buffers vibration, and the porous fiber layer absorbs mechanical vibration energy, reducing the risk of inner layer debonding. It also features a dual barrier network: an outer layer of nanofiller barrier and a middle layer of dense coating barrier, reducing oxygen permeability.

[0069] In some embodiments, the mass of the nano-silica is 5-8% of the mass of the outer high-temperature resistant barrier layer;

[0070] The mass of the nano-alumina is 3 to 5% of the mass of the outer high-temperature resistant barrier layer;

[0071] The mass of the fluorinated carbon nanotubes is 1 to 3% of the mass of the outer high-temperature resistant barrier layer.

[0072] In some embodiments, the fluorinated carbon nanotubes are treated with CF4 plasma, and the surface fluorination rate of the fluorinated carbon nanotubes is 30-50%.

[0073] The particle size of the nano-silica is 30-50 nm;

[0074] The particle size of the nano-alumina is 40–60 nm.

[0075] Nano-silica (rigidity) and fluorinated carbon nanotubes (toughness) form a "rigid-flexible" structure, maintaining impact strength while improving puncture resistance; alumina enhances wear resistance, and carbon nanotubes assist in thermal conductivity, preventing localized overheating that could lead to material softening. Simultaneously, alumina (low expansion) and PEEK (medium expansion) work synergistically, maintaining an overall coefficient of thermal expansion stable at 6 × 10⁻⁶. -6 / ℃, reducing the risk of thermal cycling stratification; the conductive network of fluorocarbon nanotubes combined with the dense barrier layer of silica / alumina provides both antistatic properties and water and oxygen barrier. In addition, the graded particle size of silica and alumina reduces the voids between fillers, improving melt flowability; the -CF2 groups of fluorocarbon nanotubes form interfacial hydrogen bonds with the ketone groups of PEEK, enhancing the bonding strength.

[0076] In some embodiments, the gradient-spun fiber layer consists of an outer layer, a middle layer, and an inner layer deposited layer by layer by an electrospinning process; wherein,

[0077] The outer layer has a nano-alumina content of 4-6%, a thickness of 8-12 μm, and a pore size of 180-200 nm.

[0078] The intermediate layer has a nano-alumina content of 8-12%, a thickness of 7-10 μm, and a pore size of 80-100 nm.

[0079] The inner layer has a nano-alumina content of 13-17%, a thickness of 5-8 μm, and a pore size of 40-60 nm.

[0080] The combination of an outer flexible fiber layer (low alumina) and an inner rigid fiber layer (high alumina) enhances tear resistance. Simultaneously, the large pore size of the outer layer supports rapid ion diffusion, while the dense structure of the inner layer inhibits dendrite growth. The gradient alumina content of the middle layer matches the thermal expansion coefficient of battery encapsulation materials (such as PEEK and HDPE), reducing the risk of delamination during thermal cycling. Furthermore, the combination of the outer layer's air permeability (200nm pore size) and the inner layer's barrier properties (40nm pore size) reduces oxygen permeability compared to a single-layer structure. This gradient-spun fiber layer, through a triple gradient design of composition, pore size, and thickness, combined with precise control of electrospinning process parameters, achieves synergistic optimization of mechanical, thermal, and electrochemical properties.

[0081] In some embodiments, the thickness of the nano-silica / polyvinylidene fluoride composite coating is 2-5 μm, and the mass ratio of the nano-silica to the polyvinylidene fluoride is 1:(4-6).

[0082] The phase change microcapsules have a particle size of 100-200 nm, a core material of paraffin / stearic acid composite, a shell material of nano-silica, and a shell thickness of 20-40 nm.

[0083] The coating thickness is 2–5 μm, and the mass ratio of nano-SiO2 to PVDF is 1:(4–6). This combines the high chemical stability of PVDF with the nano-reinforcing effect of SiO2, optimizing the mechanical strength and functionality of the coating. The addition of SiO2 increases the β-phase content of PVDF, enhancing its piezoelectric properties. Nano-SiO2 fills the pores in the PVDF matrix, forming tortuous paths and extending the diffusion paths of water and oxygen molecules. PVDF provides flexibility, while SiO2 enhances rigidity, giving the coating both scratch resistance and deformation resistance.

[0084] The microcapsules absorb heat at 80–100°C, delaying battery thermal runaway by ≥5 minutes. The nano-SiO2 shell (elastic modulus ~70 GPa) protects the core material, preventing leakage during HDPE processing.

[0085] In some embodiments, the mass fraction of vinyl acetate in the molecular chain of the ethylene-vinyl acetate copolymer is 5-40%.

[0086] Figure 2 This is a schematic flowchart illustrating a method for preparing a film material for power battery encapsulation, as provided in an embodiment of this application.

[0087] like Figure 2 As shown, this application provides a method for preparing the membrane material according to any one of the above embodiments, the method comprising the following steps:

[0088] S1. Polyether ether ketone substrate, nano silica, nano alumina and fluorinated carbon nanotubes are melt-blended using a twin-screw extruder and then hot-pressed to obtain the outer high-temperature resistant barrier layer.

[0089] S2. Nano-alumina and polyimide are dissolved in a solvent in a gradient ratio, and then the outer layer, middle layer and inner layer are sequentially deposited by multi-nozzle electrospinning to obtain the gradient transition layer.

[0090] S3. Disperse the phase change microcapsules in high-density polyethylene melt, and after cooling, coat the surface of high-density polyethylene to form a nano-silica / polyvinylidene fluoride composite coating to obtain an intermediate tear-resistant barrier layer.

[0091] S4. Mix vinyl acetate, ethylene resin and additives and extrude them, then crosslink them by electron beam irradiation to form a three-dimensional crosslinked network, and then perform hot pressing to obtain the inner adhesive layer.

[0092] S5. Using a five-layer co-extrusion equipment, the outer high-temperature resistant barrier layer, the gradient transition layer, the middle tear-resistant barrier layer, and the inner adhesive layer are formed into a four-layer structure in one step, and the layers are reinforced and bonded by maleic anhydride-grafted polypropylene to obtain a film material for power battery encapsulation.

[0093] It should be noted that a five-layer co-extrusion equipment is used to produce four functional layers (outer PEEK layer, gradient layer, middle HDPE layer, and inner adhesive layer), and MAH-g-PP adhesive layers are injected between adjacent layers through independent flow channels (a total of 5 layers). The co-extrusion molding process using the five-layer co-extrusion equipment is as follows: each extruder delivers the melt to the co-extrusion die according to the set parameters; MAH-g-PP is injected into the interfaces between adjacent layers (such as between the PEEK layer and the gradient layer, and between the gradient layer and the HDPE layer) through independent flow channels; a MAH-g-PP film with a thickness of 2-5 μm is added between each layer, accounting for 1%-2% of the total film thickness. Subsequently, the melt is layered within the die head, with the thickness of each layer controlled by a precision flow channel (outer layer 50-80μm, gradient layer 20-30μm, middle layer 80-120μm, inner layer 30-50μm). The polar groups (-COOH) of MAH-g-PP form hydrogen bonds and physical entanglements with adjacent layers (such as the ketone groups of PEEK and the non-polar chains of HDPE), increasing peel strength. Finally, the composite melt is rapidly cooled by cooling rollers (water temperature 10-15℃), with a cooling rate >50℃ / s, suppressing crystallinity (HDPE crystallinity ≤60%), improving flexibility, and achieving a winding tension ≤50N to prevent interlayer slippage or deformation.

[0094] In some embodiments, the melt blending temperature is 380–400°C;

[0095] In the electrospinning process, the concentration of the spinning solution is 15-20 wt%, the nozzle diameter is 0.3-0.5 mm, the receiving distance is 15-20 cm, and the voltage is 20-25 kV.

[0096] The electron beam irradiation dose is 12–15 kGy;

[0097] The additives include 0.1-0.5 wt% antioxidant 1010 and 0.5-1.0 wt% calcium stearate;

[0098] The die temperature of the five-layer co-extrusion equipment is 380-400℃. The interlayer bonding is enhanced by maleic anhydride-grafted polypropylene cast film. The grafting rate of the maleic anhydride-grafted polypropylene is 1.0-1.5%, and the addition amount is 1-2% of the total interlayer thickness.

[0099] The fluorinated carbon nanotubes are treated with CF4 plasma at a power of 50–100 W for 10–20 min.

[0100] In some embodiments, the method for preparing the phase change microcapsules includes:

[0101] Paraffin wax and stearic acid are melt-mixed in a 1:1 mass ratio, then added to an aqueous phase containing emulsifier, and the mixture is passed through a high-shear emulsifier to form a core material emulsion.

[0102] Sodium silicate solution was added dropwise to the core material emulsion as a silica precursor, and an interfacial hydrolysis-condensation reaction was carried out under the catalysis of ammonia water to generate a uniform silica shell and obtain a mixed solution.

[0103] The mixture was centrifuged, washed, and dried sequentially to obtain the phase change microcapsules.

[0104] In some embodiments, the emulsifier is a composite emulsifier of Span-80 / Tween-80, with a mass ratio of Span-80 to Tween-80 of 2:1, an HLB content of 12-14, and an emulsifier concentration of 3 wt%.

[0105] In some embodiments, the high-shear emulsifier operates at a speed of 15,000 rpm and an emulsification time of 10 min.

[0106] In some embodiments, the pH value of the interfacial hydrolysis-condensation reaction is 9.0-9.5, the reaction temperature is 25-30°C, and the reaction time is 2 hours; the concentration of the sodium silicate solution is 10 wt%, and tetraethyl orthosilicate is added as an auxiliary precursor, with a mass ratio of tetraethyl orthosilicate to sodium silicate of 1:5.

[0107] In summary, the technical solution provided in this application has the following advantages:

[0108] (1) Multifunctional integrated design

[0109] Synergistic high-temperature protection and thermal management: The outer high-temperature resistant material combined with the middle phase change heat absorption structure effectively delays the spread of thermal runaway and improves battery safety.

[0110] Mechanical performance optimization: Through the interlayer design that combines rigidity and flexibility, it takes into account puncture resistance, tear resistance and flexibility, and adapts to mechanical stress under complex working conditions.

[0111] Dual barrier network: The synergistic effect of nanofillers and dense coating significantly improves barrier performance and effectively prevents water and oxygen penetration.

[0112] (2) Innovation of biomimetic gradient structure

[0113] Smooth transition of thermal expansion coefficient: The gradient transition layer alleviates interlayer thermal stress and avoids the risk of delamination through gradient changes in composition and pore size.

[0114] Dynamic stress buffering: Gradient porosity structure absorbs mechanical vibration energy, improving material durability.

[0115] (3) Process efficiency and precise control

[0116] Integrated co-extrusion molding: The five-layer co-extrusion process achieves efficient integration of multi-layer structures, ensuring the strength and consistency of interlayer bonding.

[0117] Precise control of electrospinning: Multi-nozzle layer-by-layer deposition technology precisely constructs gradient pore size and composition distribution, optimizing functional adaptability.

[0118] Microcapsule controllable encapsulation: Interfacial hydrolysis-condensation process enables efficient encapsulation of phase change materials, ensuring the stability of thermal management functions.

[0119] (4) Environmental and cost advantages

[0120] Green process adaptation: Water-based microcapsule preparation, solvent-free coating and other processes reduce environmental pollution and meet the requirements of sustainable development.

[0121] Improved material utilization: Nanofillers and composite structure design reduce the amount of high-priced substrates used, achieving cost reduction and efficiency improvement.

[0122] (5) Interface stability and long-term sealing

[0123] Chemical bonding enhances adhesion: Polar compatibilizers and radiation crosslinking technology strengthen the interlayer interface, ensuring that the layers do not debond during long-term use.

[0124] Optimized corrosion resistance: The specially treated inner layer material is resistant to electrolyte corrosion, ensuring battery cycle life.

[0125] (6) Lightweight and adaptability

[0126] Thin-layer high-efficiency design: Through nano-enhancement and structural optimization, lightweight design is achieved while maintaining high performance, meeting the needs of high energy density batteries.

[0127] Wide temperature range adaptability: Material selection and modification ensure stability under all operating conditions from low temperature (-50℃) to high temperature (250℃).

[0128] This application breaks through the performance limitations of traditional packaging materials through material innovation, structural biomimicry, and process synergy, achieving a comprehensive improvement in the high-temperature protection, thermal management, mechanical strength, and interface stability of power battery packaging films. At the same time, it also has the advantages of lightweighting, environmental friendliness, and industrialization potential, providing a core material solution for the next generation of high-safety and long-life power batteries.

[0129] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards. If there is no corresponding industry standard, then common international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0130] Example 1

[0131] This embodiment provides a film material for power battery encapsulation. The layer structure of the film material, from the outside to the inside, consists of: an outer high-temperature resistant barrier layer 1, a gradient transition layer 2, a middle tear-resistant barrier layer 3, and an inner adhesive layer 4; wherein,

[0132] The outer high-temperature resistant barrier layer 1 is composed of polyetheretherketone (CAS No. 29658-26-2) substrate, nano silica, nano alumina and fluorinated carbon nanotubes (CAS No. 68647-86-9).

[0133] The gradient transition layer 2 is composed of a gradient spun fiber layer of nano-alumina and polyimide (CAS No. 62929-02-6);

[0134] The intermediate tear-resistant barrier layer 3 is a high-density polyethylene layer (high-density polyethylene (HDPE) CAS number 9002-88-4) with a nano-silica / polyvinylidene fluoride (polyvinylidene fluoride CAS number 24937-79-9) composite coating on its surface, and the high-density polyethylene layer is embedded with phase change microcapsules.

[0135] The inner adhesive layer 4 is an irradiated crosslinked ethylene-vinyl acetate copolymer layer.

[0136] The outer high-temperature resistant barrier layer 1 has a thickness of 60 μm;

[0137] The thickness of the gradient transition layer 2 is 25 μm;

[0138] The thickness of the intermediate tear-resistant barrier layer 3 is 100 μm;

[0139] The thickness of the inner adhesive layer 4 is 40 μm.

[0140] The mass of the nano-silica is 6% of the mass of the outer high-temperature resistant barrier layer 1;

[0141] The mass of the nano-alumina is 4% of the mass of the outer high-temperature resistant barrier layer 1;

[0142] The mass of the fluorinated carbon nanotubes is 2% of the mass of the outer high-temperature resistant barrier layer 1.

[0143] The fluorinated carbon nanotubes were treated with CF4 plasma, and the surface fluorination rate of the fluorinated carbon nanotubes was 40%.

[0144] The particle size of the nano-silica is 30-50 nm;

[0145] The particle size of the nano-alumina is 40–60 nm.

[0146] The gradient spun fiber layer consists of an outer layer 21, a middle layer 22, and an inner layer 23, deposited layer by layer by electrospinning process; wherein...

[0147] The outer layer 21 has a nano-alumina content of 5%, a thickness of 10 μm, and a pore size of 180–200 nm.

[0148] The intermediate layer 22 has a nano-alumina content of 10%, a thickness of 8 μm, and a pore size of 80–100 nm.

[0149] The inner layer 23 has a nano-alumina content of 15%, a thickness of 7 μm, and a pore size of 40–60 nm.

[0150] The thickness of the nano-silica / polyvinylidene fluoride composite coating is 3 μm, and the mass ratio of the nano-silica to the polyvinylidene fluoride is 1:5.

[0151] The phase change microcapsules have a particle size of 100-150 nm, a core material of paraffin / stearic acid composite, a shell material of nano-silica, and a shell thickness of 30 nm.

[0152] The ethylene-vinyl acetate copolymer has a vinyl acetate mass fraction of 20% in its molecular chain.

[0153] Based on the above-described membrane material, this embodiment also provides a method for preparing the membrane material described in the above embodiment, the method comprising the following steps:

[0154] S11. Polyether ether ketone substrate, nano silica, nano alumina and fluorinated carbon nanotubes are melt-blended using a twin-screw extruder and then hot-pressed to obtain the outer high-temperature resistant barrier layer 1.

[0155] S21. Polyimide (PI) is dissolved in DMAC solvent, and 5%-15% nano-alumina is added in stages (gradually increasing) to form spinning solutions of different concentrations. Then, spinning solutions with different alumina contents are sequentially sprayed out through a multi-channel electrospinning device to form a fiber layer with a gradient distribution of pore size. The outer layer 21, the middle layer 22 and the inner layer 23 are sequentially deposited to obtain the gradient transition layer 2.

[0156] S31. Phase change microcapsules are dispersed in high-density polyethylene melt, and after cooling, nano-silica / polyvinylidene fluoride composite coating is formed on the surface of high-density polyethylene to obtain intermediate tear-resistant barrier layer 3.

[0157] S41. Mix vinyl acetate, ethylene resin and additives and extrude them, then crosslink them by electron beam irradiation to form a three-dimensional crosslinked network, and then perform hot pressing to obtain the inner adhesive layer 4.

[0158] S51. Using a five-layer co-extrusion equipment, the outer high-temperature resistant barrier layer 1, the gradient transition layer 2, the intermediate tear-resistant barrier layer 3, and the inner adhesive layer 4 are formed into a four-layer structure in one step, and the layers are reinforced and bonded together with maleic anhydride-grafted polypropylene (commercial model Exxelor PO 1020) to obtain a film material for power battery encapsulation.

[0159] The melt blending temperature is 400°C;

[0160] In the electrospinning process, the spinning solution concentration is 18wt%, the nozzle diameter is 0.4mm, the receiving distance is 16cm, and the voltage is 22kV.

[0161] The electron beam irradiation dose was 14 kGy;

[0162] The adjuvants include 0.3 wt% antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) and 0.8 wt% calcium stearate;

[0163] The die temperature of the five-layer co-extrusion equipment is 400℃. The interlayer bonding is enhanced by maleic anhydride-grafted polypropylene cast film. The grafting rate of the maleic anhydride-grafted polypropylene is 1.2%, and the addition amount is 1.5% of the total interlayer thickness.

[0164] The fluorinated carbon nanotubes were treated with CF4 plasma at a power of 70W for 15 minutes.

[0165] The preparation method of the phase change microcapsules includes: melting and mixing paraffin wax (CAS No. 8002-74-2) and stearic acid (CAS No. 57-11-4) in a 1:1 mass ratio, then adding the mixture to an aqueous phase containing an emulsifier, and forming a core material emulsion using a high-shear emulsifier; adding sodium silicate solution as a silica precursor dropwise to the core material emulsion, and performing an interfacial hydrolysis-condensation reaction under ammonia catalysis to generate a uniform silica shell, resulting in a mixture; and centrifuging, washing, and drying the mixture sequentially to obtain the phase change microcapsules. The emulsifier is a Span-80 / Tween-80 composite emulsifier, with a Span-80 to Tween-80 mass ratio of 2:1, an HLB of 12-14, and an emulsifier concentration of 3 wt%. The high-shear emulsifier operates at 15000 rpm for 10 min. The pH value of the interfacial hydrolysis condensation reaction is 9.0-9.5, the reaction temperature is 30℃, and the reaction time is 2h; the concentration of the sodium silicate solution is 10wt%, and tetraethyl orthosilicate is added as an auxiliary precursor, with a mass ratio of tetraethyl orthosilicate to sodium silicate of 1:5.

[0166] Example 2

[0167] This embodiment provides a film material for power battery encapsulation. The layer structure of the film material, from the outside to the inside, consists of: an outer high-temperature resistant barrier layer 1, a gradient transition layer 2, a middle tear-resistant barrier layer 3, and an inner adhesive layer 4; wherein,

[0168] The outer high-temperature resistant barrier layer 1 is composed of polyetheretherketone (CAS No. 29658-26-2) substrate, nano silica, nano alumina and fluorinated carbon nanotubes (CAS No. 68647-86-9).

[0169] The gradient transition layer 2 is composed of a gradient spun fiber layer of nano-alumina and polyimide (CAS No. 62929-02-6);

[0170] The intermediate tear-resistant barrier layer 3 is a high-density polyethylene layer (high-density polyethylene (HDPE) CAS number 9002-88-4) with a nano-silica / polyvinylidene fluoride (polyvinylidene fluoride CAS number 24937-79-9) composite coating on its surface, and the high-density polyethylene layer is embedded with phase change microcapsules.

[0171] The inner adhesive layer 4 is an irradiated crosslinked ethylene-vinyl acetate copolymer layer.

[0172] The outer high-temperature resistant barrier layer 1 has a thickness of 80 μm;

[0173] The thickness of the gradient transition layer 2 is 30 μm;

[0174] The thickness of the intermediate tear-resistant barrier layer 3 is 120 μm;

[0175] The thickness of the inner adhesive layer 4 is 50 μm.

[0176] The mass of the nano-silica is 8% of the mass of the outer high-temperature resistant barrier layer 1;

[0177] The mass of the nano-alumina is 5% of the mass of the outer high-temperature resistant barrier layer 1;

[0178] The mass of the fluorinated carbon nanotubes is 3% of the mass of the outer high-temperature resistant barrier layer 1.

[0179] The fluorinated carbon nanotubes are treated with CF4 plasma, and the surface fluorination rate of the fluorinated carbon nanotubes is 50%.

[0180] The particle size of the nano-silica is 30-50 nm;

[0181] The particle size of the nano-alumina is 40–60 nm.

[0182] The gradient spun fiber layer consists of an outer layer 21, a middle layer 22, and an inner layer 23, deposited layer by layer by electrospinning process; wherein...

[0183] The outer layer 21 has a nano-alumina content of 6%, a thickness of 12 μm, and a pore size of 180–200 nm.

[0184] The intermediate layer 22 has a nano-alumina content of 12%, a thickness of 10 μm, and a pore size of 80–100 nm.

[0185] The inner layer 23 has a nano-alumina content of 17%, a thickness of 8 μm, and a pore size of 60 nm.

[0186] The thickness of the nano-silica / polyvinylidene fluoride composite coating is 5 μm, and the mass ratio of the nano-silica to the polyvinylidene fluoride is 1:6.

[0187] The phase change microcapsules have a particle size of 100-200 nm, a core material of paraffin / stearic acid composite, a shell material of nano-silica, and a shell thickness of 40 nm.

[0188] The ethylene-vinyl acetate copolymer has a vinyl acetate mass fraction of 40% in its molecular chain.

[0189] Based on the above-described membrane material, this embodiment also provides a method for preparing the membrane material described in the above embodiment, the method comprising the following steps:

[0190] S11. Polyether ether ketone substrate, nano silica, nano alumina and fluorinated carbon nanotubes are melt-blended using a twin-screw extruder and then hot-pressed to obtain the outer high-temperature resistant barrier layer 1.

[0191] S21. Polyimide (PI) is dissolved in DMAC solvent, and 5%-15% nano-alumina is added in stages (gradually increasing) to form spinning solutions of different concentrations. Then, spinning solutions with different alumina contents are sequentially sprayed out through a multi-channel electrospinning device to form a fiber layer with a gradient distribution of pore size. The outer layer 21, the middle layer 22 and the inner layer 23 are sequentially deposited to obtain the gradient transition layer 2.

[0192] S31. Phase change microcapsules are dispersed in high-density polyethylene melt, and after cooling, nano-silica / polyvinylidene fluoride composite coating is formed on the surface of high-density polyethylene to obtain intermediate tear-resistant barrier layer 3.

[0193] S41. Mix vinyl acetate, ethylene resin and additives and extrude them, then crosslink them by electron beam irradiation to form a three-dimensional crosslinked network, and then perform hot pressing to obtain the inner adhesive layer 4.

[0194] S51. Using a five-layer co-extrusion equipment, the outer high-temperature resistant barrier layer 1, the gradient transition layer 2, the intermediate tear-resistant barrier layer 3, and the inner adhesive layer 4 are formed into a four-layer structure in one step, and the layers are reinforced and bonded together with maleic anhydride-grafted polypropylene (commercial model ExxelorPO1020) to obtain a film material for power battery encapsulation.

[0195] The melt blending temperature is 400°C;

[0196] In the electrospinning process, the spinning solution concentration is 20wt%, the nozzle diameter is 0.5mm, the receiving distance is 20cm, and the voltage is 25kV.

[0197] The electron beam irradiation dose was 15 kGy;

[0198] The additives include 0.5 wt% antioxidant 1010 and 1.0 wt% calcium stearate;

[0199] The die temperature of the five-layer co-extrusion equipment is 380℃. The interlayer bonding is enhanced by maleic anhydride-grafted polypropylene cast film. The grafting rate of the maleic anhydride-grafted polypropylene is 1.0%, and the addition amount is 1% of the total interlayer thickness.

[0200] The fluorinated carbon nanotubes were treated with CF4 plasma at a power of 100W for 10 minutes.

[0201] The preparation method of the phase change microcapsules includes: melting and mixing paraffin wax (CAS No. 8002-74-2) and stearic acid (CAS No. 57-11-4) in a 1:1 mass ratio, then adding the mixture to an aqueous phase containing an emulsifier, and forming a core material emulsion using a high-shear emulsifier; adding sodium silicate solution as a silica precursor dropwise to the core material emulsion, and performing an interfacial hydrolysis-condensation reaction under ammonia catalysis to generate a uniform silica shell, resulting in a mixture; and centrifuging, washing, and drying the mixture sequentially to obtain the phase change microcapsules. The emulsifier is a Span-80 / Tween-80 composite emulsifier, with a Span-80 to Tween-80 mass ratio of 2:1, an HLB of 12-14, and an emulsifier concentration of 3 wt%. The high-shear emulsifier operates at 15000 rpm for 10 min. The pH value of the interfacial hydrolysis condensation reaction is 9.0-9.5, the reaction temperature is 30℃, and the reaction time is 2h; the concentration of the sodium silicate solution is 10wt%, and tetraethyl orthosilicate is added as an auxiliary precursor, with a mass ratio of tetraethyl orthosilicate to sodium silicate of 1:5.

[0202] Example 3

[0203] This embodiment provides a film material for power battery encapsulation. The layer structure of the film material, from the outside to the inside, consists of: an outer high-temperature resistant barrier layer 1, a gradient transition layer 2, a middle tear-resistant barrier layer 3, and an inner adhesive layer 4; wherein,

[0204] The outer high-temperature resistant barrier layer 1 is composed of polyetheretherketone (CAS No. 29658-26-2) substrate, nano silica, nano alumina and fluorinated carbon nanotubes (CAS No. 68647-86-9).

[0205] The gradient transition layer 2 is composed of a gradient spun fiber layer of nano-alumina and polyimide (CAS No. 62929-02-6);

[0206] The intermediate tear-resistant barrier layer 3 is a high-density polyethylene layer (high-density polyethylene (HDPE) CAS number 9002-88-4) with a nano-silica / polyvinylidene fluoride (polyvinylidene fluoride CAS number 24937-79-9) composite coating on its surface, and the high-density polyethylene layer is embedded with phase change microcapsules.

[0207] The inner adhesive layer 4 is an irradiated crosslinked ethylene-vinyl acetate copolymer layer.

[0208] The outer high-temperature resistant barrier layer 1 has a thickness of 50 μm;

[0209] The thickness of the gradient transition layer 2 is 20 μm;

[0210] The thickness of the intermediate tear-resistant barrier layer 3 is 80 μm;

[0211] The thickness of the inner adhesive layer 4 is 30 μm.

[0212] The mass of the nano-silica is 5% of the mass of the outer high-temperature resistant barrier layer 1;

[0213] The mass of the nano-alumina is 3% of the mass of the outer high-temperature resistant barrier layer 1;

[0214] The mass of the fluorinated carbon nanotube is 1% of the mass of the outer high-temperature resistant barrier layer 1.

[0215] The fluorinated carbon nanotubes are treated with CF4 plasma, and the surface fluorination rate of the fluorinated carbon nanotubes is 30%.

[0216] The particle size of the nano-silica is 30-50 nm;

[0217] The particle size of the nano-alumina is 40–60 nm.

[0218] The gradient spun fiber layer consists of an outer layer 21, a middle layer 22, and an inner layer 23, deposited layer by layer by electrospinning process; wherein...

[0219] The outer layer 21 has a nano-alumina content of 4%, a thickness of 8 μm, and a pore size of 180–200 nm.

[0220] The intermediate layer 22 has a nano-alumina content of 8%, a thickness of 7 μm, and a pore size of 80–100 nm.

[0221] The inner layer 23 has a nano-alumina content of 13%, a thickness of 5 μm, and a pore size of 40–60 nm.

[0222] The thickness of the nano-silica / polyvinylidene fluoride composite coating is 2 μm, and the mass ratio of the nano-silica to the polyvinylidene fluoride is 1:4.

[0223] The phase change microcapsules have a particle size of 100-200 nm, a core material of paraffin / stearic acid composite, a shell material of nano-silica, and a shell thickness of 20 nm.

[0224] The mass fraction of vinyl acetate in the molecular chain of the ethylene-vinyl acetate copolymer is 5%.

[0225] Based on the above-described membrane material, this embodiment also provides a method for preparing the membrane material described in the above embodiment, the method comprising the following steps:

[0226] S11. Polyether ether ketone substrate, nano silica, nano alumina and fluorinated carbon nanotubes are melt-blended using a twin-screw extruder and then hot-pressed to obtain the outer high-temperature resistant barrier layer 1.

[0227] S21. Polyimide (PI) is dissolved in DMAC solvent, and 5%-15% nano-alumina is added in stages (gradually increasing) to form spinning solutions of different concentrations. Then, spinning solutions with different alumina contents are sequentially sprayed out through a multi-channel electrospinning device to form a fiber layer with a gradient distribution of pore size. The outer layer 21, the middle layer 22 and the inner layer 23 are sequentially deposited to obtain the gradient transition layer 2.

[0228] S31. Phase change microcapsules are dispersed in high-density polyethylene melt, and after cooling, nano-silica / polyvinylidene fluoride composite coating is formed on the surface of high-density polyethylene to obtain intermediate tear-resistant barrier layer 3.

[0229] S41. Mix vinyl acetate, ethylene resin and additives and extrude them, then crosslink them by electron beam irradiation to form a three-dimensional crosslinked network, and then perform hot pressing to obtain the inner adhesive layer 4.

[0230] S51. Using a five-layer co-extrusion equipment, the outer high-temperature resistant barrier layer 1, the gradient transition layer 2, the intermediate tear-resistant barrier layer 3, and the inner adhesive layer 4 are formed into a four-layer structure in one step, and the layers are reinforced and bonded together with maleic anhydride-grafted polypropylene (commercial model ExxelorPO1020) to obtain a film material for power battery encapsulation.

[0231] The melt blending temperature is 380°C;

[0232] In the electrospinning process, the spinning solution concentration is 15wt%, the nozzle diameter is 0.3mm, the receiving distance is 15cm, and the voltage is 25kV.

[0233] The dose of electron beam irradiation was 12 kGy;

[0234] The additives include 0.1 wt% antioxidant 1010 and 0.5 wt% calcium stearate;

[0235] The die temperature of the five-layer co-extrusion equipment is 400℃. The interlayer bonding is enhanced by maleic anhydride-grafted polypropylene cast film. The grafting rate of the maleic anhydride-grafted polypropylene is 1.5%, and the addition amount is 1% of the total interlayer thickness.

[0236] The fluorinated carbon nanotubes were treated with CF4 plasma at a power of 50W for 10 minutes.

[0237] The preparation method of the phase change microcapsules includes: melting and mixing paraffin wax (CAS No. 8002-74-2) and stearic acid (CAS No. 57-11-4) in a 1:1 mass ratio, then adding the mixture to an aqueous phase containing an emulsifier, and forming a core material emulsion using a high-shear emulsifier; adding sodium silicate solution as a silica precursor dropwise to the core material emulsion, and performing an interfacial hydrolysis-condensation reaction under ammonia catalysis to generate a uniform silica shell, resulting in a mixture; and centrifuging, washing, and drying the mixture sequentially to obtain the phase change microcapsules. The emulsifier is a Span-80 / Tween-80 composite emulsifier, with a Span-80 to Tween-80 mass ratio of 2:1, an HLB of 12-14, and an emulsifier concentration of 3 wt%. The high-shear emulsifier operates at 15000 rpm for 10 min. The pH value of the interfacial hydrolysis condensation reaction is 9.0-9.5, the reaction temperature is 30℃, and the reaction time is 2h; the concentration of the sodium silicate solution is 10wt%, and tetraethyl orthosilicate is added as an auxiliary precursor, with a mass ratio of tetraethyl orthosilicate to sodium silicate of 1:5.

[0238] Comparative Example 1

[0239] This comparative example is based on the disclosure in Example 1, with the following modifications:

[0240] The membrane material does not have an outer high-temperature resistant barrier layer 1 in its layer structure.

[0241] Comparative Example 2

[0242] This comparative example is based on the disclosure in Example 1, with the following modifications:

[0243] No gradient transition layer 2 is set in the layer structure of the membrane material.

[0244] Comparative Example 3

[0245] This comparative example is based on the disclosure in Example 1, with the following modifications:

[0246] No intermediate tear-resistant barrier layer is provided in the layer structure of the membrane material.

[0247] Comparative Example 4

[0248] This comparative example is based on the disclosure in Example 1, with the following modifications:

[0249] The membrane material does not have an inner adhesive layer in its layer structure.

[0250] The performance of the films used for power battery encapsulation obtained in Examples 1-3 and Comparative Examples 1-4 was measured, and the results are shown in Table 1. The specific performance measurement methods are as follows:

[0251] Thermal decomposition temperature: Thermogravimetric analysis (TGA) was used to record the temperature at which the mass decreased by 5% under a nitrogen atmosphere at a heating rate of 10℃ / min.

[0252] Water and oxygen transmission rate: The multi-channel water and oxygen transmission rate test device was used to simulate the battery packaging environment (85℃ / 85%RH) and tested according to GB / T21529-2008 standard.

[0253] Tensile strength: The longitudinal / transverse tensile strength was tested using a universal testing machine according to ASTM D882 standard at a tensile rate of 50 mm / min.

[0254] Phase change enthalpy: The melting enthalpy of the core material was determined using a differential scanning calorimeter (DSC) at a heating rate of 5 °C / min.

[0255] Table 1 shows the performance of the film materials used for power battery encapsulation in Examples 1-3 and Comparative Examples 1-4.

[0256]

[0257] As shown in Table 1, the thermal decomposition temperature of the membrane materials in Examples 1-3 is ≥400℃, and the water and oxygen permeability is ≤0.01g / (m²). 2 •day), tensile strength ≥80MPa, puncture strength ≥500N / mm, interlayer peel strength ≥8N / 15mm, phase change enthalpy ≥120J / g, high-temperature buffer time elongation ≥30%. The embodiment achieves synergistic optimization of thermal stability, mechanical strength, and interface bonding through a multilayer composite design, meeting the high-standard requirements of power battery packaging.

[0258] In Comparative Example 1, the absence of PEEK substrate and fluorinated carbon nanotubes, relying solely on HDPE (melting point ~130℃), resulted in accelerated thermal degradation, poor thermal stability, and weak water and oxygen barrier properties.

[0259] In Comparative Example 2, the lack of a gradient transition layer prevents heat from spreading evenly, leading to localized heat accumulation that disrupts the phase change buffer, uneven heat distribution, and low utilization of the phase change material.

[0260] In Comparative Example 3, the lack of SiO2 / PVDF coating and phase change microcapsules meant that the EVA alone could not withstand the battery expansion stress, resulting in insufficient mechanical strength and easy puncture and breakage.

[0261] In Comparative Example 4, the irradiated cross-linked EVA layer was missing, and the interlayer relied solely on maleic anhydride-grafted PP, which could not resist electrolyte corrosion, resulting in poor interfacial bonding and easy delamination failure.

[0262] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0263] Furthermore, in the description of this application, the terms "comprising," "including," etc., mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0264] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A film material for encapsulating power batteries, characterized in that, The membrane material has the following layer structure from the outside to the inside: an outer high-temperature resistant barrier layer, a gradient transition layer, a middle tear-resistant barrier layer, and an inner adhesive layer; wherein, The outer high-temperature resistant barrier layer is composed of polyetheretherketone substrate, nano-silica, nano-alumina and fluorinated carbon nanotubes; The gradient transition layer is composed of a gradient spun fiber layer of nano-alumina and polyimide; The intermediate tear-resistant barrier layer is a high-density polyethylene layer with a nano-silica / polyvinylidene fluoride composite coating on the surface, and phase change microcapsules are embedded in the high-density polyethylene layer. The inner adhesive layer is an irradiated cross-linked ethylene-vinyl acetate copolymer layer; The gradient spun fiber layer is composed of an outer layer, a middle layer, and an inner layer deposited layer by layer by electrospinning process; wherein, The outer layer has a nano-alumina content of 4-6%, a thickness of 8-12 μm, and a pore size of 180-200 nm. The intermediate layer has a nano-alumina content of 8-12%, a thickness of 7-10 μm, and a pore size of 80-100 nm. The inner layer has a nano-alumina content of 13-17%, a thickness of 5-8 μm, and a pore size of 40-60 nm.

2. The membrane material according to claim 1, characterized in that, The thickness of the outer high-temperature resistant barrier layer is 50–80 μm; The thickness of the gradient transition layer is 20–30 μm; The thickness of the intermediate tear-resistant barrier layer is 80–120 μm; The thickness of the inner adhesive layer is 30–50 μm.

3. The membrane material according to claim 1, characterized in that, The mass of the nano-silica is 5-8% of the mass of the outer high-temperature resistant barrier layer; The mass of the nano-alumina is 3-5% of the mass of the outer high-temperature resistant barrier layer; The mass of the fluorinated carbon nanotube is 1 to 3% of the mass of the outer high-temperature resistant barrier layer.

4. The membrane material according to claim 3, characterized in that, The fluorinated carbon nanotubes are treated with CF4 plasma, and the surface fluorination rate of the fluorinated carbon nanotubes is 30-50%. The particle size of the nano-silica is 30-50 nm; The particle size of the nano-alumina is 40–60 nm.

5. The membrane material according to claim 1, characterized in that, The thickness of the nano-silica / polyvinylidene fluoride composite coating is 2-5 μm, and the mass ratio of the nano-silica to the polyvinylidene fluoride is 1:(4-6). The phase change microcapsules have a particle size of 100-200 nm, a core material of paraffin / stearic acid composite, a shell material of nano-silica, and a shell thickness of 20-40 nm.

6. The membrane material according to claim 1, characterized in that, The mass fraction of vinyl acetate in the molecular chain of the ethylene-vinyl acetate copolymer is 5-40%.

Citation Information

Patent Citations

  • Flexible encapsulating film systems

    CN104327758A

  • Lithium battery diaphragm for power battery and preparation method thereof

    CN106935772A